FINANCIAL STABILITY LEVEL ON BANKING INDUSTRY Comparative Analysis Between Islamic and Conventional Bank In Indonesia - Alvien Nur Amalia (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
Financial stability in the banking industry is important because it is a dynamicand high-risk industry. The purpose of this study was to compare the stability ofIslamic and conventional banking in Indonesia by assessing the level of volatility ofReturn on Assets (ROAV), managerial stability which can be seen from the value ofTobin’s Q, Non-Performing Loans/ Financing and liquidity in both of banking andusing 11 Islamic banks and 11 conventional banks as samples. The quarterly secondarydata was used in the observation start in 2011 and will end in 2013 using paneldata regression. The results of the study explained that there are several factors, bothinternal banks factors consist of banking profit before tax, credits to total assets ratio,the ratio of loss reserves to total financing, operating expenses to income operationalratio and macroeconomic factors include the level of the exchange rate rupiah toUSD, BI Rate, and GDP growth are significantly influence the financial stability ofIslamic and conventional banking. The conclusion indicates that the level of financialstability of Islamic banking is still lower than conventional banking.